Investigating and preventing ankle sprain - Fong, D. T.-P. (Sports innovation, technology and research, 2016)
Ankle sprain injury is very common in sports. Without proper care, an ankle sprained for five or more times can be more prone to chronic ankle instability. In severe condition, it may lead to articular cartilage defect, early joint osteoarthritis and deformity, which may ultimately need surgical treatment to reconstruct, or to replace with an artificial joint. Besides research on the treatment and rehabilitation, it is also worth conducting research on its prevention. Sports biomechanists can contribute in injury prevention, by analysing injury aetiology and mechanism, designing preventive intervention, and evaluating the effectiveness in a biomechanics laboratory [1]. Since 2004, I and my research team (Figure 4.1) in the Sport Performance and Biomechanics Laboratory at Department of Orthopaedics and Traumatology, The Chinese University of Hong Kong had been investigating and preventing sport-related ankle ligamentous sprain injury…